Eksistensi Filsafat Hukum dalam Mewujudkan Kepastian dan Keadilan Hukum: The Existence of Legal Philosophy in Realizing Legal Certainty and Justice - Revintalis Osilia Mahar (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
The philosophy of law is a branch of science that examines the nature, purpose, and values ??underlying the existence of law. This study is important because law functions not only to create certainty but also to realize justice in society. This research aims to explain the concept of the philosophy of law, analyze the relationship between legal philosophy and legal certainty and justice, and examine its role in realizing these two values. The research uses a normative legal method with a library research approach. Data were obtained from books, scientific journals, academic articles, and relevant laws and regulations, then analyzed descriptively and qualitatively. The results show that the philosophy of law plays a crucial role as a foundation for the formation, interpretation, and enforcement of law. The philosophy of law also serves to bridge the balance between legal certainty and legal justice, so that the law not only provides order but also fulfills society's sense of justice. Thus, the philosophy of law plays a crucial role in realizing a just, certain, and beneficial legal system.